In chronic spontaneous urticaria, high numbers of dermal endothelial cells, but not mast cells, are linked to recurrent angio‐oedema. (24th October 2017) - Terhorst, D.; Koti, I.; Krause, K.; Metz, M.; Maurer, M.
Summary: Background: Chronic spontaneous urticaria (CSU) is an inflammatory skin disorder characterized by recurrent weals, angio‐oedema or both. Recent studies have shown that the number of endothelial cells is increased in the skin of patients with CSU, but the underlying mechanisms and clinical implications of this are unclear. Aim: To evaluate whether mast cell (MC) or endothelial cell (EC) numbers correlate with CSU and whether they are relevant for disease duration, disease activity or the presence of clinical features. Methods: We determined the numbers of CD31+ ECs and MCs in nonlesional skin of 30 patients with CSU using quantitative histomorphometry, and assessed their correlation with each other and with clinical features such as disease duration, disease activity and occurrence of angio‐oedema. Results: The numbers of MCs and ECs were high in the nonlesional skin of patients with CSU, but did not correlate with each other. Neither MC number nor EC number correlated with disease duration or disease activity. Interestingly, patients with high numbers of cutaneous CD31+ ECs had higher rates of recurrent angio‐oedema and vice versa . Conclusions: Based on these findings, we speculate that vascular remodelling and MC hyperplasia in patients with CSU occurs independently and via different mechanisms. Targeting of the mechanisms that drive neoangiogenesis in CSU may result in novel therapeutic strategies for the management of patients with angio‐oedema.